A rare case of progressive multifocal leukoencephalopathy - As a presenting manifestation of AIDS - S Sumangala; Mohd Zeeshan Ali; Mushtaq Saudagar (Wolters Kluwer Medknow Publications, 2020)
Progressive multifocal leukoencephalopathy (PML) is a fatal demyelinating central nervous system (CNS) infection disease that exclusively affects immunocompromised individuals. John Cunningham virus, the etiologic agent for PML, is ubiquitous in the general population but rarely causes disease in immunocompetent hosts. Here, we present a 35-year-old male with left hemiparesis and loss of vision, diagnosed as PML as the first AIDS-defining event, with previously undiagnosed human immunodeficiency virus (HIV) infection. PML is an underinvestigated CNS infection seen in HIV patients usually with advanced disease. We present an unusual case report, where PML occurred as the first AIDS-defining event in a patient with previously undiagnosed HIV infection. This case is presented to enlighten the physicians regarding the clinical entity of PML to be suspected in HIV-infected patients who present with focal neurologic deficits even in undiagnosed infection.